Cultural Transposition: Adapting an Appreciative Inquiry to Support Organisational Change in a Non-Western Context - Sabra, Nabil (AUT Graduate Research School and Te Mātāpuna: AUT Library, 2025)
This doctoral research study employed an Appreciative Inquiry as a culturally adjusted method for enabling six university educators to develop critical thinking (ijtihad) in Yemeni graphic design education.[1] Emanating from a constructivist paradigm, the study recognised the role of sociocultural contexts in knowledge formation. The Appreciative Inquiry was divided into four stages (Discovery, Dream, Design, and Destiny) based on Cooperrider and Whitney’s (2005) model. The study utilised Virtual Communities of Practice (VCoP)[2] based on a traditional cultural construct known as Halakat Elm (حلقات علم, knowledge circles). These circles were shaped by three cultural principles: wa’adeuk fa’ajbuh (واذا دعاك فأجبه); Husn al-Dhann (حسن الظن); and sadakat al elm (صدقة العلم). Key themes were identified through a Reflexive Thematic Analysis (RTA). The outcomes demonstrated that an Appreciative Inquiry developed inside the culturally specific construct of the Halakat Elm can serve as an effective, culturally responsive approach for developing co-creative approaches to organisational and pedagogical reform.   [1] The project was granted ethics approval (21/129) on July 8, 2021. [2] A Virtual Community of Practice (VCoP) operates online. Here, individuals engage in instruction-based learning or group discussions within a specific domain, forming social structures to facilitate knowledge sharing and creation (Wenger-Trayner, 2015).
Keywords: 3903 Education Systems; 35 Commerce, Management, Tourism and Services; 39 Education; Minority Health; Appreciative Inquiry; Critical thinking; Halakat Elm; Ijtihad; Virtual Community of Practice (VCoP)